Implementing Achmea: The Quest for Fundamental Change in International Investment La (Polish Yearbook of International Law, 2021)
The judgment of the Court of Justice in the Achmea case evoked significant repercussions regarding the application and operation of the bilateral investment treaties (BITs) concluded between EU Member States. As a result of this decision, EU Member States have decided to terminate almost 190 intra-EU BITs. Nevertheless, full implementation of the Achmea judgment remains a complex issue, entangled in political and legal controversies concerning intra-EU BITs which have been present for more than a decade. On a more general level, the implementation process is simultaneously entwined in two other significant debates: the specifics of the rights of investors, and the relationship between EU law and international law.